7 - Book Reviews: « Administration for Development in Nigeria ,» edited by Paul COLLINS, published by African Education Press, 8 Denton Street, Ebute Metta, Lagos, August 1980, 337 pages, price: N 6.50, paperback. - HEINECKE, H. (Africa Development, 1981)
P. HEINECKE, Faculty of Administration Ahmadu Bello University, Zaria, Nigeria